Short Communication: Cave-dwelling Arthropod community of Semedi Show Cave in Gunungsewu Karst Area, Pacitan, East Java, Indonesia - ISMA DWI KURNIAWAN; CAHYO RAHMADI; REZZY EKO CARAKA; TIARA E. ARDI (Society for Indonesian Biodiversity, 2018)
Kurniawan ID, Rahmadi C, Caraka RE, Ardi TE. 2018. Short Communication: Cave-dwelling Arthropod community of Semedi Show Cave in Gunungsewu Karst Area, Pacitan, East Java, Indonesia. Biodiversitas 19: 857-866. Arthropods are a major group of animals which have significant roles in maintaining cave ecosystem stability. Semedi is a new show cave, but information about arthropods in this cave was not available. The use of cave as a tourist attraction will bring environmental changes which potentially disturb cave-dwelling arthropod community. This study aimed to measure arthropod diversity and their relation to abiotic factors in Semedi Show Cave. Arthropods were sampled by hand collecting, a combination of pitfall and bait traps, and Berlese extractor. Abiotic factors measured were climatic and edaphic parameters. Sampling was conducted in the 3 zones of Semedi cave (Entrance, Twilight, and Dark). Data were analyzed by calculation of richness (Margalef), diversity and evenness (Shannon-Wiener) indices, cluster and correlation analyses. A total 1095 individuals of arthropods consisting of 102 morphospecies, belonging to 6 Classes, and 19 Orders were sampled during this study. The entrance zone had higher richness and diversity indices (richness=12.80, diversity=3.40) than the twilight zone  (richness=7.85, diversity=3.25) and the dark zone  (richness=5.35, diversity=2.63). Meanwhile, the twilight zone had higher evenness index (0.85) than the entrance zone (0.77) and the dark zone (0.77). Each zone of Semedi cave had different abiotic conditions. Abiotic conditions and Arthropod communities in the twilight and dark zones were more similar to each other than to those of the entrance zone. The statistical analyses showed that there were significant correlations between abiotic factors and arthropod communities. Semedi had various cave-dwelling arthropods. Sustainable management of show cave should be applied to minimize the destructive impact of tourism activities on the cave arthropod community.